TRANSPARANSI PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA KEPENGHULUAN DI DESA SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Nurwidia "; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The rural areas across Indonesia have been predicted that locals will be given APBKep or local government budget comes from two main sources such as local central and districts government. The reason of giving local government budget is to assist locals becoming independent society. Thus, the rural is equal to central people. In line with this situation, local government should bring into reality the aims of making the developed and prosperous village by using the concept of transparency in administering the local budget and society. The purpose of this research is to knowthe transparency of local government budget and income of Sungai Segajah village Kubu District Rokan Hilir Regency. Also, this research used the concept of “The Princple Of-Opened-Transparency” that is adopted from Mustofa Widjaja in (Irvan, 2017). This research is known as descriptive qualitative. The samples were selected using purpose sampling technique. The result of this research proved that transparency in administering local government budget in Sungai Segajah village in Kubu Rokan Hilir does not work maximally because there are still obstacles that become problems of local government in planning and implementing the transparency of local government budget. *Keywords: Transparency, Administration, Local Government Budget